2017
DOI: 10.2174/1570159x14666160325121145
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic System and Post-translational Modifications: An Insight on the Role in Alzheimer's Disease

Abstract: BackgroundBackground: Alzheimer’s disease (AD) is the most common form of old age dementia. The formation of amyloid plaques (Aβ), neurofibrillary tangles and loss of basal forebrain cholinergic neurons are the hallmark events in the pathology of AD.Literature ReviewCholinergic system is one of the most important neurotransmitter system involved in learning and memory which preferentially degenerates in the initial stages of AD. Activation of cholinergic receptors (muscarinic and nicotinic) activates multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 186 publications
(217 reference statements)
0
23
0
1
Order By: Relevance
“…Choline acetyltransferase activity is greatly reduced in individuals with AD. It has also been shown that acetyl cholinesterase (AChE) accelerates the aggregation of Aβ [108]. The degeneration of serotonergic neurons in the raphe nucleus and noradrenergic neurons in the locus coeruleus mediates on cognitive symptoms associated with AD [109].…”
Section: Pathophysiological Mechanisms Of Alzheimer's Diseasementioning
confidence: 99%
“…Choline acetyltransferase activity is greatly reduced in individuals with AD. It has also been shown that acetyl cholinesterase (AChE) accelerates the aggregation of Aβ [108]. The degeneration of serotonergic neurons in the raphe nucleus and noradrenergic neurons in the locus coeruleus mediates on cognitive symptoms associated with AD [109].…”
Section: Pathophysiological Mechanisms Of Alzheimer's Diseasementioning
confidence: 99%
“…It is defined as the primary degenerative process that can damage cholinergic neurons in the brain and results in cognitive impairment. Neurofibrillary alterations and β‐amyloid pathology interact with cholinergic receptors and accelerate the progression of AD . The cholinergic hypothesis has served the basis for the majority of treatment strategies and drug development approaches toward AD till date.…”
Section: Introductionmentioning
confidence: 99%
“…Post‐translational modification of APP has been a focus of research in the field of AD, including examinations of APP glycosylation, ubiquitination, and phosphorylation (Marcelli et al, ). These modifications have been proposed as regulatory mechanisms to affect APP trafficking and cleavage, signal transduction, and axonal outgrowth (Ahmed, Zahid, Mahboob, & Farhat, ; Ando, Iijima, Elliott, Kirino, & Suzuki, ; Schedin‐Weiss, Winblad, & Tjernberg, ). Since APP processing and Aβ production involve intracellular fragment transport and vesicle trafficking, APP processing can be regulated via modulating its phosphorylation.…”
Section: Discussionmentioning
confidence: 99%